What Forest Knows - Lyon, George Ella 1949-; Hall, August (New York : Atheneum Books for Young Readers, 2014)
Follows the changing seasons in a forest as trees and animals are nourished and are dependent on each other.
"A Richard Jackson Book."
AD500L
Decoding demand: 70 (high)
Semantic demand: 80 (high)
Syntactic demand: 67 (high)
Structure demand: 75 (high)
Keywords: Trees; Juvenile fiction; Forest ecology; Juvenile fiction; Ecology; Juvenile fiction; Nature stories; Seasons; Juvenile fiction; Trees; Fiction; Forest ecology; Fiction; Ecology; Fiction; Nature stories; Seasons; Fiction